Breaking Boundaries: A Study on the Innovative Network Strategies of Canadian SMEs Expanding into Unfamiliar Markets - Qutob, Anas; Ye, Yu Wei (Journal of Comparative International Management)

(untitled) (Management Futures, 2024)
Small and medium-sized enterprises (SMEs) rely on network ties to facilitate overseas expansion. However, the expansion may be hindered when geographical and institutional distance is great, and boundaries of network connections are reached since the information from those networks may be distorted and lack objectivity. Nevertheless, Canadian SMEs with native-born owners have succeeded in expanding into geographically and institutionally distant markets despite possessing no pre-existing ties. Drawing on insights from institution- and network-based views, we investigate this understudied issue through a generic inductive interview of six Canadian SMEs that have either expanded into or plan expansion into the United Arab Emirates in which they had no pre-existing ties. Results reveal that all firms understood that institutional differences affect the business environment. They embarked on a distinct networking approach, focusing on broadening their existing network in the early stage and making full use of outsourcing networking activities. The research helps pave the way for further clarity and understanding of the dynamic nature of international entrepreneurship when relating to distant yet commercially attractive markets.